SOS1 tonoplast neo-localization and the RGG protein SALTY are important in the extreme salinity tolerance of Salicornia bigelovii - Salazar, Octavio R; Chen, Ke; Melino, Vanessa J; Reddy, Muppala P; Hřibová, Eva; Čížková, Jana; Beránková, Denisa; Arciniegas Vega, Juan Pablo; Cáceres Leal, Lina María; Aranda, Manuel; Jaremko, Lukasz; Jaremko, Mariusz; et al. (Nature communications, 2024)
The identification of genes involved in salinity tolerance has primarily focused on model plants and crops. However, plants naturally adapted to highly saline environments offer valuable insights into tolerance to extreme salinity. Salicornia plants grow in coastal salt marshes, stimulated by NaCl. To understand this tolerance, we generated genome sequences of two Salicornia species and analyzed the transcriptomic and proteomic responses of Salicornia bigelovii to NaCl. Subcellular membrane proteomes reveal that SbiSOS1, a homolog of the well-known SALT-OVERLY-SENSITIVE 1 (SOS1) protein, appears to localize to the tonoplast, consistent with subcellular localization assays in tobacco. This neo-localized protein can pump Na+ into the vacuole, preventing toxicity in the cytosol. We further identify 11 proteins of interest, of which SbiSALTY, substantially improves yeast growth on saline media. Structural characterization using NMR identified it as an intrinsically disordered protein, localizing to the endoplasmic reticulum in planta, where it can interact with ribosomes and RNA, stabilizing or protecting them during salt stress.
Keywords: salinita; Sodium Chloride; Salt Tolerance; Vacuoles; vakuoly; tolerance k soli; chlorid sodný; Plant Proteins; Nicotiana; Salt Stress; Endoplasmic Reticulum; proteomika; Chenopodiaceae; rostlinné proteiny; solný stres; Proteomics; Gene Expression Regulation, Plant; regulace genové exprese u rostlin; transkriptom; Salinity; endoplazmatické retikulum; Transcriptome; tabák